2013
DOI: 10.1111/cas.12132
|View full text |Cite|
|
Sign up to set email alerts
|

Sorafenib suppresses growth and survival of hepatoma cells by accelerating degradation of enhancer of zeste homolog 2

Abstract: Enhancer of zeste homolog 2 (EZH2) is a mammalian histone methyltransferase that contributes to the epigenetic silencing of target genes that regulate cancer cell growth and survival. It is overexpressed in hepatocellular carcinoma (HCC) with a clinical significance that remains obscure. Sorafenib, a multikinase inhibitor, has been used as a first-line therapeutic drug and shown clinical efficiency for advanced-stage HCC patients. In the present study, we found that sorafenib lowered the protein level of EZH2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Studies have demonstrated that the expression of some histone methyltransferases, such as EZH2 [59] , contribute to the epigenetic silencing of target genes that regulate cancer cell growth and survival, which have been associated with sorafenib resistance of HCC cells. EZH2 knockdown or EZH2 inhibition treatment promoted sorafenib-induced hepatoma cell growth arrest and apoptosis.…”
Section: Epigenetic Regulation Involved In Drug Resistancementioning
confidence: 99%
“…Studies have demonstrated that the expression of some histone methyltransferases, such as EZH2 [59] , contribute to the epigenetic silencing of target genes that regulate cancer cell growth and survival, which have been associated with sorafenib resistance of HCC cells. EZH2 knockdown or EZH2 inhibition treatment promoted sorafenib-induced hepatoma cell growth arrest and apoptosis.…”
Section: Epigenetic Regulation Involved In Drug Resistancementioning
confidence: 99%
“…Protein extraction from cultured cells or tissues, immunoblotting, and immunoprecipitation were carried out as previously described. 31,51 Antibodies used here included those against GAPDH, PAK1, EZH2, H3K27me3, p300, HDAC-1, H3K9me3, and H3K4me3 (Santa Cruz Biotechnology, Santa Cruz, CA, USA). Chromatin immunoprecipitation was carried out with the ChIP Assay Kit (Millipore, Billerica, MA, USA) according to instructions.…”
Section: Pak1 Dictates Inflammatory Macrophage Polarization W Zhang Ementioning
confidence: 99%
“…Risk factor for HCC are mainly HBV infection, HCV infection, excessive alcohol consumption, and dietary exposure to aflatoxin [3]. Current treating methods, such as surgical resection, radiofrequency ablation (RFA) and transhepatic arterial chemotherapy and embolization (TACE) only control the patient with early HCC [4]. Thus the early diagnosis and early treatment is critical for HCC patients.…”
mentioning
confidence: 99%